Effect of robot for medication management on home care professionals' use of working time in older people's home care: A non-randomized controlled clinical trial - Kajander-Unkuri Satu; Vaismoradi Mojtaba; Katajisto Jouko; Kangasniemi Mari; Turjamaa Riitta (BMC, 2025)
Background
Medication management has a key role in the daily tasks of home care professionals delivered to older
clients in home care. The aim of this study was to examine the effect of using a robot for medication management on home care professionals´ use of working time.
Methods
A pragmatic non-randomized controlled clinical trial was conducted. The participants were home care
professionals who carried out home care clients’ medication management. Home care clients were allocated into intervention groups (IG) and control groups (CG) (n = 64 and 46, respectively) based on whether or not they received the robot. Data were collected using the Working Time Tracking Form prior to and 1 and 2 months after introducing the intervention. The t-test was used to compare the groups at each three timepoints. Analysis of Covariance was used to examine the groups’ differences for the total time for medications as the number of visits per day as the covariate.
Results
With robot use, the total amount of home visits decreased by 89.4% and 92.4% after 1 and 2 months of
intervention use, respectively, compared to pre-intervention (p < 0.001). The total working time used for medication management considering the number of visits per day decreased from 54.2 min (95% CI 49.6–58.8) to 34.9 min (31.4–38.3), i.e., by slightly over 19 min (p < 0.001) in the IG group. During the follow-up, the total working time used for medication management considering the number of visits per day remained the same in the CG group.
Conclusion
Using a robot for medication management had a notable effect on decreasing the use of working time
of home care professionals. For health services, decreased use of working time for medication management means that the time saved can be assigned to services that cannot be replaced otherwise. More digital solutions should be developed based on home care clients’ and professionals’ needs to meet the challenge of the growing number of older people in need of home care and ensure their safety.
Trial registration ClinicalTrials.gov Identifier: NCT05908604 retrospectively registered (18/06/2023).
Keywords Home-care professional, Medication management, Older people’s home care, Patient safety, Robot, Working time